Ståndortsanpassad växtanvändning på bjälklag - Lindström, Per (2009)
The purpose for this essay is to investigate claims trees and shrubs have to survive and grow on concrete roof foundation and create good design from those conditions. At first is described what requirements there are on the planting areas to make it comfortable for the plants. After that is a planting list with chosen plants that is supposed to survive on the concrete roof presented. Then is the site and its presumptions presented. Finally my design is presented and is continued with a discussion and reflection about the essay and the knowledge gained from it. The difficulty as I can see with the essay has been for example to know exactly what plant's that grows and survive on the site that I have chose for my design. It's not really until you have tried the plant's on the site as you can say for real if they are going to like the spot or not. It is such narrow margins for the plants to survive on, as places on roofs can be such extreme situations. The extreme situation makes it also very interesting for the design.